The effect of liquidity on the profitability and value of banks listed on Iraq stock market (An analytical study) - Abed Al Ogaili, Sabah Hassan (Journal of Economics and Administrative Sciences, 2020)
The purpose of the study is to analyze the extent of the impact of liquidity as an independent variable on profitability as an intermediate variable and the value of banks listed in the Iraq Stock Exchange as a dependent variable, as the research problem is summarized by the fact that most banks focus on profitability as a phased goal without focusing on maximizing its value as a strategic goal by enhancing the wealth of owners and shareholders. On the long term, the research community is represented by the banks listed on the Iraq Stock Exchange, while the research sample was deliberately chosen, which included three private banks such as Baghdad Commercial Bank, the Iraqi Commercial Bank and the Iraqi Investment Bank, and the researcher used the applied analytical approach through the use of a set of methods The financial and statistical analysis in conducting the analysis process for the banks, the research sample, and the results of the analysis also showed the validity of the sub-hypotheses, namely the presence of a statistically significant correlation and an adverse effect between liquidity and profitability, as well as the existence of an adverse statistically significant correlation and influence between the profit and the value of the bank.